Answer this
kindly NO SPAM
Thank you
Attachments:
![](https://hi-static.z-dn.net/files/db4/a21b89470465a4ac1bae94f32e21f134.jpg)
Answers
Answered by
9
Answer:
Option(a)
Step-by-step explanation:
Given a,b,c are in GP.
Since a,b and c are in G.P, we have, a * c = b² ----- (i)
Now,
Given: a(b² + c²) - c(a² + b²)
= ab² + ac² - a²c - b²c
= a(ac) + ac² - a²c - (ac)c {From (i)}
= a²c + ac² - a²c - ac²
= 0
Hope it helps!
Anonymous:
Thanks a lot ...
Similar questions
Art,
7 months ago
Social Sciences,
7 months ago
English,
7 months ago
Math,
1 year ago
Science,
1 year ago